(untitled) (LTU Journal of Advanced Computing & Engineering, 2026)
This study examines the influence of social media advertisement, trust, access to information, and reviews on consumer purchase decisions. The research is quantitative in nature, employing a structured questionnaire to collect primary data from a sample of 150 active social media users within the Kathmandu Valley. A simple random sampling (SRS) method was utilized. The data analysis was conducted using SPSS, employing descriptive statistics, Correlation, ANOVA, and Regression analysis. The findings reveal that social media advertisement and reviews have a positive and significant impact on consumers purchase decisions. Conversely, the results suggest that access to information and trust have no significant impact on the purchase decision of consumers in the studied sample. Thus, this study contributes to the limited research in the context of Nepalese consumers.